Desenvolvimento de catalisadores nanoestruturados a base de nanotubos de titanatos aplicados a conversão de CO2 e CH4 - Monteiro, Wesley Formentin (2019)
The need for processes capable of mitigating CO2 (main greenhouse gas), such as the conversion of CO2, has been highlighted. Among the possibilities, the conversion of CO2 into organic carbonates, or their use, together with CH4 to obtain syngas is promising approaches. Thus, the development of nanostructured catalysts efficient in the CO2 molecule activation or in the C-H bond break of CH4 has been studied. The use of nanostructures has been shown to be important, since besides the particular properties of the nanoscale, it is possible to modify the morphology of these, generating a versatility of applications. Thus, the morphological modification of titanium dioxide nanoparticles in titanate nanotubes (TNT) leads to a new material with high specific surface area and the possibility of designing the nanostructure through modification and / or functionalization resulting in the development of new hybrid materials. In this context, this work aim the development of nanostructured catalysts based on titanate nanotubes functionalized with ionic liquid (LI), or modified with different metals evaluating their efficiency in the conversion of CO2 to organic carbonates and in the production of syngas. The results show that the hybrid nanostructures (TNT / LI) were efficient for the conversion of CO2 into different cyclic organic carbonates, presenting yield greater than 80% with selectivities close to 100%. The nickel-modified TNTs were efficient in the synthesis of syngas, generating CO2 and CH4 conversions of up to 70% with H2/CO ratio close to 1. In addition, the presence of sodium in the TNT structure provided high resistance to coke formation.